EVALUASI PERGESERAN STRUKTUR EKONOMI KOTA BENGKULU - Sunoto Sunoto; Bertha Iin Esti Indraswanti (Convergence: The Journal of Economic Development, 2020)
The purpose of this research was to evaluate the shifting of economic structure of  Bengkulu City. Base on BPS secondary time series data (2011-2019), descriftive analysis was used to evaluate the shifting economic structure. The result of this research was concluded that the economis structure was gradually shifting in secondary and tertier sector. The different variable and the amount of data usage in this analysis had different result in leading sectors. The first periods of 2014-2017, Bengkulu City has 10 leading sectors, and the second period of this research become 7 sectors. It was used PDRB data, and become 4 leading sectors when employment data used merely. When the data of PDRB and employment was combined to analyze the Bengkulu City leading sector, it’s just become 3 sectors. So the economy of Bengkulu City was dominated by the Providing Accommodation, Food and Drink sector, the Real Estate sector and the Education Sector.